2015
DOI: 10.1155/2015/239506
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Gastroenteritis: Case Report and Review in Search for Diagnostic Key Points

Abstract: Eosinophilic gastroenteritis is considered an uncommon disease with a low incidence rate that remains as a diagnostic challenge for the clinician, in spite of the fact that seventy years have passed since its original description. Hereby we present the case of a 29-year-old male without history of allergies who was evaluated for unspecific gastrointestinal symptoms, without relevant findings on physical examination and presenting an initial complete blood count (CBC) with severe eosinophilia. The patient was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
1
14
0
3
Order By: Relevance
“…The recently reported incidence of eosinophilic gastroenteritis is estimated to be 28 per 100,000 per year, and studies have shown an increased prevalence during the past 16 years [3]. The pathogenesis of eosinophilic gastroenteritis involves a Type 1 hypersensitivity reaction, and many patients will have a history of atopy [8]. The associated allergic disorders, including asthma, allergic rhinitis, and atopic eczema are present in between 54–63% of reported cases of eosinophilic gastroenteritis [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently reported incidence of eosinophilic gastroenteritis is estimated to be 28 per 100,000 per year, and studies have shown an increased prevalence during the past 16 years [3]. The pathogenesis of eosinophilic gastroenteritis involves a Type 1 hypersensitivity reaction, and many patients will have a history of atopy [8]. The associated allergic disorders, including asthma, allergic rhinitis, and atopic eczema are present in between 54–63% of reported cases of eosinophilic gastroenteritis [7].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of eosinophilic gastroenteritis requires the presence of three main features that include gastrointestinal symptoms, eosinophilia of one or more areas of the gastrointestinal tract on histology, and the exclusion of other causes of tissue eosinophilia, including intestinal tuberculosis, parasitosis, and malignancy [5,7]. Although the clinical history and physical examination are important, the definitive diagnosis of eosinophilic gastroenteritis is made histologically, which requires gastrointestinal biopsy [8]. To confirm the histological diagnosis, at least 15–20 eosinophils per high power microscopic field are required [5].…”
Section: Discussionmentioning
confidence: 99%
“…[4] Eosinophilic gastrointestinal disorders affect all ethnic groups between 20 and 50 years of age but more commonly around the third decade of life. [5] Unlike in the esophagus, baseline eosinophils are detected in the stomach and intestine under healthy conditions as a part of the host-defense mechanism. [15] However, their infiltration to the deeper layers is considered abnormal.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Unlike in the esophagus, baseline eosinophils are detected in the stomach and intestine under healthy conditions as a part of the host-defense mechanism. [15] However, their infiltration to the deeper layers is considered abnormal. Eosinophilia in the intestinal mucosa is not seen with infections caused by common bacteria, viruses, and fungus.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is based on a high index of suspicion when patients present with GI symptoms along with laboratory and pathological findings suggestive of GI tract infiltration by eosinophils [5]. …”
Section: Discussionmentioning
confidence: 99%